Forage cactus (Opuntia ficus-indica Mill) meal in rabbit diets in the growth phase - PASCOAL,Leonardo Augusto Fonseca (2020)
ABSTRACT Two experimental tests were carried out to evaluate the inclusion of forage cactus meal in diets for rabbits during the growth phase. In the first test 14 male New Zealand red rabbits were used, housed in metal cages, and distributed in a completely randomly design with two treatments and seven replicates with one animal per experimental unit. The digestibility of the nutrients and the digestible energy of the forage cactus meal were determined by the total feces collection method. The forage cactus meal presented 92.24% of DM, 5.63% of CP and 2,347 kcal of DE/kg. In the second test the inclusion of 0, 10, 20 and 30% forage cactus meal in the rabbit diet was tested for productive performance, carcass characteristics, viscera and economic viability. Thus, 40 male rabbits of the New Zealand red breed were used, distributed in metal cages, completely random designed with four treatments, five replicates and two animals per experimental unit. No influence of inclusion levels (P>0.05) on performance variables, housing characteristics or economic viability was observed. The forage cactus meal can be included in up to 30% in the diets of growing rabbits.